HapNetworkView: a tool for haplotype network exploration and visualization - Lianjiang Chi; Yi Dong; Ruizhen Wang; Suiyuan Yang; Lan Wu; Yongbiao Xue; Hua Chen (BMC Genomics)
Abstract Background Haplotype networks are useful for investigating the genealogical relationships among haplotypes and have been extensively used in molecular evolution and population genetic studies. However, existing tools for visualizing haplotype networks lack comprehensive functionalities for data exploration and layout adjustments. Therefore, there is a need for a useful tool capable of constructing and visualizing haplotype networks, facilitating the exploration of data, particularly with datasets with large sample sizes. Results We present HapNetworkView, a user-friendly tool that facilitates the construction and interactive visualization of haplotype networks, enabling users to explore haplotypes and mutation information effectively. HapNetworkView offers both automatic optimization and manual adjustment for haplotype network layouts. Additionally, HapNetworkView supports various input and output formats, as well as color customization. Conclusions These comprehensive functionalities collectively satisfy various needs of users in haplotype network analysis, making HapNetworkView a valuable tool.